Asset Recovery in Corruption Crimes - Wardani, Dian Eka Kusuma (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2024)
Efforts to return stolen state assets (stolen asset recovery) through criminal acts of corruption (TIPIKOR) tend not to be easy to carry out. Corruption perpetrators have extraordinarily wide and difficult access to hide or launder money from the proceeds of their criminal acts of corruption. The problem becomes increasingly difficult for recovery efforts because the haven for the proceeds of crime extends beyond the borders of the country where the criminal act of corruption was committed. This research aims to determine the mechanism for returning assets in criminal acts of corruption through criminal channels. The type of research used is normative research, and the data collection technique is library research. The research results show that the mechanism for returning assets in criminal acts of corruption through criminal channels has four stages: tracking assets, freezing or confiscating assets, confiscating assets, and returning and handing over assets to the victim's country.